"Threads of the Orientalist/Procolonial discourse in John Updike's novel The Coup" - Sayyid, Farouq Rezq Bekhit (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper is an attempt to point out how John Updike’s novel The Coup (1978) conforms to the traditional Western notions and conventions about Africa and Africans. The methodology of this paper involves a textual analysis of The Coup whereby significant passages from the novel are cited and elucidated with regard to the ideas of Orientalism as a discourse to reveal how Updike employs such a discourse to render a distorted image of Africa and African cultures as he draws heavily on stereotypes and traditional prejudices as embodiment of the darker side of the human psyche. At the same time, this paper is meant to point out the seemingly authoritative stance of Updike through the sources he consults and the techniques he utilizes to endow his negative discourse with a tone of authority, knowledge, and expertise. This seemingly authentic stance provides Updike with the means to adopt a superior, Western voice of power in the creation of truth with regard to Africa as a nation and to the East/West relationship as a dichotomy. As the novel relates, Updike not only justifies the American intervention in Africa, but he does injustice to the humanity of the African personality which he diminished through racist stereotyping. It is, therefore, through utilizing this Orientalist/postcolonial approach and relevant data that this paper concludes that Updike displays absolutely no insight into the characters involved in this novel. Instead, he weaves African colonialism, Islam, the Cold War, socialism, capitalism, and exploitation of every variety into a novel with a few too many characters that are explored just enough to make them into two-dimensional cartoons of real human beings. As such, Updike's The Coup is no more than an attempt to assert the authority of the West, specifically the United States, as a superpower that surpasses the Soviet Union in its control over Africa and African resources.